Endophytic Fungi Isolated from Rhizophora mucronata and Their Antibacterial Activity - Kustiariyah Tarman; Dwi Safitri; Iriani Setyaningsih (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
Mangrove plants are known as source of traditional medicines. Endophytic fungi have an important economic potential for antibacterial, enzyme and secondary metabolites that are useful especially in pharmaceutical industry. The purpose of this research was to determine the antibacterial activity of the endophytic fungal extracts from mangrove plant Rhizophora mucronata against diarrhea causing bacteria. This research included isolation, characterization, cultivation, extraction, and antibacterial activity test. The study yielded 5 types of endophytic fungi with different morphology. Endophytic fungus DS1 was the selected isolate based on antagonism test. The growth pattern showed the stationary phase of isolate DS1 was on the 15th day. Culture broth extract showed considerable inhibition on Pseudomonas aeruginosa with diameter of inhibition zone was 18.5 mm ± 3.32. Extract of mycelium inhibited the growth of Staphylococcus aureus (2 mm). The culture broth extract showed more potent antibacterial activity in comparison with the mycelium extract.